(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The aim of this article is to introduce the reader to some street games of the Central Asian Dungans and their role in the development of intellectual, physical, and communicative abilities. Borrowed games are one of the cultural elements that help to understand the mechanisms of the socio-cultural aspects of interethnic contacts, which create a shared domestic and cultural environment for the entire population living in the same region or country.